Penerapan Model Pembelajaran Kooperatif Tipe STAD Untuk Meningkatkan Hasil Belajar Prakarya dan Kewirausahaan (Rekayasa) Peserta Didik - Syarifah Maisar (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Research objectives (1) To improve the learning outcomes of crafts and entrepreneurship (Engineering) students of class XI IPS 1 MAN Nagan Raya through a STAD type cooperative learning model (2) To increase the activities of teachers and students of class XI IPS 1 MAN Nagan Raya in the teaching and learning process using the STAD type cooperative learning model. In this study, the subject of the study was all students of Class XI IPS 1 MAN Nagan Raya for the 2022/2023 academic year with a total of 29 students. The data collection method uses final tests, interview tests, observations, Learner responses and field notes. The data collected includes data on teacher activities, student activities, student learning outcomes and Student responses. The results showed (1) Student learning outcomes increased from the first cycle with an average score of 67.93% increased to 76.20% in the second cycle, (2) Teacher activity increased, the first cycle percentage value was 79.04% to 90.47% in the second cycle while student activity increased, the first cycle with a percentage value of 65.62% to 84.37% in the second cycle.